2015
DOI: 10.1098/rsta.2014.0261
|View full text |Cite
|
Sign up to set email alerts
|

Wave heating of the solar atmosphere

Abstract: One contribution of 13 to a Theo Murphy meeting issue 'New approaches in coronal heating' . Magnetic waves are a relevant component in the dynamics of the solar atmosphere. Their significance has increased because of their potential as a remote diagnostic tool and their presumed contribution to plasma heating processes. We discuss our current understanding of coronal heating by magnetic waves, based on recent observational evidence and theoretical advances. The discussion starts with a selection of observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
143
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(144 citation statements)
references
References 191 publications
(282 reference statements)
1
143
0
Order By: Relevance
“…However, as recent observations have revealed that significant wave power is present in (closed) coronal loops, wave heating mechanisms are regaining the attention of the solar physics community [14]. An important point to note here is that (observed) wave damping does not automatically imply dissipation, and hence heating, as the two processes could potentially operate on very different spatial and temporal scales.…”
Section: Modelling Coronal Heatingmentioning
confidence: 99%
See 3 more Smart Citations
“…However, as recent observations have revealed that significant wave power is present in (closed) coronal loops, wave heating mechanisms are regaining the attention of the solar physics community [14]. An important point to note here is that (observed) wave damping does not automatically imply dissipation, and hence heating, as the two processes could potentially operate on very different spatial and temporal scales.…”
Section: Modelling Coronal Heatingmentioning
confidence: 99%
“…In recent years, there has been a wealth of observations of various waves and oscillations in the corona [14]. As well as potentially being directly involved in heating, the detection of waves and oscillations has opened up the field of coronal seismology, potentially allowing parameters such as magnetic field strengths to be inferred (see [15] for a recent review).…”
Section: (A) Advances In Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from being important agents for atmospheric heating (see e.g., Klimchuk 2006;Parnell & De Moortel 2012;Arregui 2015;De Moortel & Browning 2015, for some recent reviews), these waves and oscillations can also be exploited in the context of solar magneto-seismology (SMS) to infer the atmospheric parameters that are difficult to directly measure (for early ideas that laid the foundation of this practice, see Uchida 1970, Rosenberg 1970, Zajtsev & Stepanov 1975, Roberts et al 1984; also see recent reviews by e.g., Nakariakov & Verwichte 2005, Roberts 2008, Erdélyi & Goossens 2011, Nakariakov et al 2016. For instance, "high-frequency" fast waves with periods of order seconds were theoretically shown to play an important role in heating the solar corona (e.g., Porter et al 1994b,a).…”
Section: Introductionmentioning
confidence: 99%